The Puppet Theater for Learning of Local History - Rotjanasuksomboon, Anukoon; Ser, Shaw Hong; Sontinuch, Teekapat (Journal of Ecohumanism, 2024)
The research on puppetry for learning local history aims to create a puppet show that provides knowledge about local history. It is a story from the past of local people. They should learn about the history of the community because it is the root of the community. It is a way to learn about identity and create pride. In this creative research, the researcher aims to study the history of Phraek Si Racha, Sankhaburi District, Chai Nat Province, which has evidence from the reign of Phra Intharacha of Ayutthaya. The researcher studied information from documents and went to the field to survey information to compile a puppet show script to provide knowledge about Phra Intharacha through puppetry.Puppetry is a performance made from materials that imitate humans and animals in size and proportion, approximately 50 centimeters high. The head is cast in resin; the face is painted to look human, with arms on both sides. The body is made of cylindrical PVC pipes, and the person is wearing a cloth bag as a shirt and moving to imitate humans. Phra Intharacha, the sixth monarch of Ayutthaya, ruled for 15 years. He had three sons. The first son was named Chao Ai Phraya, who ruled Suphan Buri. The second son was Chao Yi Phraya, who ruled Phraek Si Racha. The third king was Chao Sam Phraya. He ruled Phitsanulok. The Chao Phraya River is an important river flowing through Chainat Province, branching into Mae Nam Noi, flowing through Sankhaburi District, Singburi Province, Ang Thong Province, Phra Nakhon Si Ayutthaya Province, and joining the Chao Phraya River in Phra Nakhon Si Ayutthaya Province. Another branch of the Chao Phraya River flows through Wat Sing District, Chainat Province, called Makham Thao River, through Suphan Buri Province, called Suphan River, through Nakhon Pathom Province, called Nakhon Chai Si River, and through Samut Sakhon Province, called Tha Chin River. The puppet show of Phra Intharacha used 30 secondary school students from Kuruprachasan School, Sankhaburi District, Chainat Province, which is a local historical community group, through the process of learning the story of Phra Intharacha and learning how to manipulate puppets. The show was performed in the school so the students could learn about Phra Intharacha and understand it. 1,795 students watched the show. The show was performed by the school’s executives and local executives. Moreover, the parents watched the performance of 100 people. Thirty groups of performers assessed their knowledge and understanding of the content of the performance. The results were that some people understood the content before watching the performance. The average summary score was 4.26/10. After watching the performance, 8.1/10 people understood the content. Overall, this puppet show, which was used to learn local history, was successful.